Direct Synthesis of H2O2 on Pd Based Catalysts: Modelling the Particle Size Effects and the Promoting Role of Polyvinyl Alcohol. Issue 1 (31st October 2018) - Giorgianni, Gianfranco; Abate, Salvatore; Centi, Gabriele; Perathoner, Siglinda
Abstract: Sol immobilization is a relevant preparation method, particularly for the preparation of Pd‐based catalysts for the direct synthesis of H2 O2 . In this preparation, polyvinyl alcohol (PVA) acts as capping agent for Pd particles. Modelling the role of PVA on the Pd nanoparticle size and its promoting effect on the selectivity is important to understand better these catalysts. Here, Pd based catalysts prepared by sol immobilization have been tested in a semi‐batch reactor with an H2 /O2 ratio ≈1, analysing the influence of the Pd nanoparticle size and the effect of PVA on the rate constants of the reaction network and their change during the reaction. A stepwise testing protocol coupled with transmission electron microscopy characterization as a function of reaction time has been used. These catalysts were compared with other catalysts prepared by hydrazine reduction and impregnation‐decomposition, where PVA is absent. The results are analysed in terms of rate constants for the various rates in the reaction network in relation with the Pd average particle size and related sites distribution, as a function of the changes occurring during extended catalytic tests. The SI‐series of catalysts (prepared by sol‐immobilization) shows enhanced properties, attributed to the effect of PVA capping agent in forming less defective Pd nanoparticles. This induces both a decrease of direct combustion and secondary hydrogenolysis reactions, and an enhancement of the direct synthesis route. The PVA layer limits H2 O2 back‐diffusion with a negative influence on the productivity and selectivity, with its removal leading to initial enhanced performances, but in long‐term to a worsening due to sintering of Pd nanoparticles in extended operations. Abstract : Straight to the point : The role of polyvinyl alcohol (PVA) capping agent for Pd nanoparticles active in H2 O2 direct synthesis is studied and kinetically modelled to single out the different effects in modifying the catalytic performances. PVA enhances the properties leading to less defective Pd nanoparticles, inducing both a decrease of direct combustion and secondary hydrogenolysis reactions, and an enhancement of the direct synthesis route.